The transformation of the clothing industry in China - Zhang, M.; Kong, X.X.; Chenayah, S. (Taylor & Francis, 2016)
This article examines the transformation of clothing manufacturing in China with a focus on institutional support, technological upgrading and global production chains. Evidence shows that reforms and integration into global production chains have rapidly expanded China's exports but these have also driven the relocation abroad of Chinese clothing firms. Global integration has motivated clothing firms to upgrade through learning, adoption and innovation. Hence, despite improvements in technological capabilities the share of clothing value-added in manufacturing has gradually declined. Also, China has increasingly faced industrial structural change from clothing to the capital goods, real estate and high-tech sectors.